(untitled) (Scientific journal of the Fergana State University, 2024)
This study investigates the comprehensive assessment of Lemna minor, a floating aquatic plant, by examining its biological and morphological characteristics, species composition, and dissolved oxygen levels. The research aims to provide a detailed understanding of the ecological attributes of Lemna minor and its potential impact on aquatic ecosystems. Species composition is assessed to identify coexisting species and understand the plant’s ecological interactions. Dissolved oxygen levels are measured to evaluate the plant’s influence on water quality and its potential role in oxygen dynamics within aquatic environments. The findings of this study contribute valuable insights into the ecological significance of Lemna minor, aiding in the development of informed conservation and management strategies for aquatic ecosystems.